Avaliação de um teste in house de PCR-colorimétrico em placa para o diagnóstico de Tuberculose Pulmonar - Rivero, Martha Gabriela Celle [UNIFESP] (2008)
The techniques most widely used in the routine laboratory diagnosis of pulmonary tuberculosis (PTB) show variable sensitivities. Various nucleic acids amplification tests have been proposed for the rapid diagnosis of PTB in association with the acid-fast bacillus staining, culture and clinical diagnosis. We evaluated the performance of an in-house colorimetric PCR test using the IS6110 sequence in samples of sputum, broncho-alveolar lavage and tracheal aspirate from 150 patients with clinical suspicion of PTB admitted to a General University Hospital in the period from March to December 2005. The colorimetric PCR test was applied to non-processed samples (NPS) and to the sediment. The validity of the test was estimated in comparison with culture and clinical diagnosis of PTB. The sensitivity of the in house colorimetric PCR test was 41.93% (NPS) and 48.38% (sediment) and specificity 98.21% (NPS) and 97.67% (sediment). The in house colorimetric PCR test had a good agreement, kappa = 0.6, in comparison to the acid-fast staining and kappa = 0.5 when compared to culture. Considering the clinical diagnosis, sensitivity was 28.6% (NPS and sediment) and specificity 98.2% (NPS) and 97.3% (sediment). The positive and negative predictive values were 83.3% and 81.1% for NPS and 76.9% and 81.2% for sediment, respectively. The in house colorimetric PCR test showed low sensitivity, high specificity and good agreement compared with acid-fast bacillus staining and culture used for diagnosis of PTB in a routine microbiology laboratory at a General University Hospital The test also showed high predictive values (positive and negative) and high positive post-test probability when the clinical diagnosis was considered.